2018
DOI: 10.3390/rs10020347
|View full text |Cite
|
Sign up to set email alerts
|

Combining Multi-Date Airborne Laser Scanning and Digital Aerial Photogrammetric Data for Forest Growth and Yield Modelling

Abstract: The increasing availability of highly detailed three-dimensional remotely-sensed data depicting forests, including airborne laser scanning (ALS) and digital aerial photogrammetric (DAP) approaches, provides a means for improving stand dynamics information. The availability of data from ALS and DAP has stimulated attempts to link these datasets with conventional forestry growth and yield models. In this study, we demonstrated an approach whereby two three-dimensional point cloud datasets (one from ALS and one f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(89 citation statements)
references
References 37 publications
1
87
0
1
Order By: Relevance
“…While LiDAR-derived forest inventory can provide inventory data to make sound commercial thinning decisions, any forest inventory becomes less accurate and useful as the years since data acquisition increase. To increase the longevity of LiDAR-derived inventory and reduce the costs associated with LiDAR acquisition, processing, and inventory predictions, simplified process-based and size-class growth models have been used to forecast stand-level variables at grid-cell resolution [28][29][30]. In addition, tree-level variables have been forecasted using tree lists imputed for LiDAR grid cells and a tree-list growth model [31].…”
Section: Introductionmentioning
confidence: 99%
“…While LiDAR-derived forest inventory can provide inventory data to make sound commercial thinning decisions, any forest inventory becomes less accurate and useful as the years since data acquisition increase. To increase the longevity of LiDAR-derived inventory and reduce the costs associated with LiDAR acquisition, processing, and inventory predictions, simplified process-based and size-class growth models have been used to forecast stand-level variables at grid-cell resolution [28][29][30]. In addition, tree-level variables have been forecasted using tree lists imputed for LiDAR grid cells and a tree-list growth model [31].…”
Section: Introductionmentioning
confidence: 99%
“…This effect increased with the decrease of accuracy of the T1 and T2 models, which was especially pronounced for the indirectly derived ∆BA and ∆V. Though the accuracy of the individual models for BA and V at T1 and T2 was on par with accuracies reported in the literature for similar forest stand conditions [24,50], the analyses show that this level of accuracy was insufficient for determining growth in these stand conditions.…”
Section: Discussionmentioning
confidence: 65%
“…For example, Lamb et al [23] demonstrated how ALS-predicted stand attributes can be matched with a library of plot-level measurements and used as inputs for a locally calibrate tree-list growth model. Forest stand attributes predicted with point cloud data can also be integrated with stand-level growth models by generating a database of growth curves and using cell-level predictions to identify the most suitable growth curve [24,52]. Though such approaches benefit from a bi-temporal dataset, they can be used with a single ALS acquisition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations